Retrospective Study: Diagnosis and Management of Vulvovaginalis Candidiasis - Ditta Harnindya; Indropo Agusni (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Vulvovaginalis candidiasis (VVC) is an infection of the vaginal mucosa and or vulva caused by Candida species. As many as 70-75% of women are infected by CVV at least once during their lifetime, which most often occurs in women of childbearing age. Purpose: To evaluate the general overview of new VVC patients at the Sexual Transmitted Infection Division Dermato-Venereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya from the period of 2010-2012. Methods: This is a retrospective study, and evaluating medical records of new CVV patients including basic information, history taking, physical and laboratory examination, management, follow up, and counseling. Result: There were 325 new CVV patients (11.5%) from the total 2.813 patients from the total of new patients at the STI Division Dermato-Venereology Outpatient Dr. Soetomo General Hospital Surabaya, range of age was mostly 25-44 years old (53.2%) and 257 (79.1%) patients were married. The most main complaint was vaginal discharge accompanied with itchy sensation in 213 (65.5%) patients. The most vaginal discharge appearance was white like cottage cheese in 245 (75.3%) patients. From the wet mount 220 (67.7%) patients showed either blastospore or pseudohyphae, while from the gram stain 220 (67.7%) patients showed 217 (66.8%) patients showed either blastospore or pseudohyphae. Therapy with ketoconasol is in 239 (73.2%) patients. Conclusion: Appropriate diagnosis, adequate therapy, also risk factors exploration and counseling are very important in the management of VVC.Key words: Vulvovaginalis candidiasis, fluor albus, itch, pseudohyphae, ketoconazole.